How to manage the perfect wave: Surfing tourism management in the Mentawai Islands, Indonesia. (January 2016) - Towner, Nick
Abstract: Sustainable marine tourism management is significantly assisted by the involvement of all relevant stakeholder groups including the local community. Co-management is an effective approach to marine tourism management in Indonesia, integrating government policy, sound business practices, customary laws and local territorial rights. This paper examines the current management approach to the Mentawai Islands surfing tourism industry by exploring multiple stakeholder perspectives. Field research was conducted in the period between July and September of 2010, through 108 in-depth interviews with surfing tourists, surf operators, government officials and NGO employees. The paper indicates that surfing tourists, resort and charter boat operators and local community perceived that the current management of the Mentawai surfing tourism industry was inadequate at protecting the marine resources it was based on. A key finding of this paper was that stakeholders identified that ingrained government corruption has led to a failure of the current surf tourism management scheme. In conclusion corruption, coordination of government resources, securing the trust of stakeholders, and incorporating local community knowledge into the management framework are seen as the major barriers to effective management of the Mentawai Islands surfing tourism industry. Highlights: Perceptions of relevant stakeholder in the Mentawai surfing tourism industry are explored. Stakeholders perceive management framework to be inadequate. Corruption, limited government resources, trust and community involvement identified as the major barriers. Co-management is found to be the most effective approach to surfing tourism management.